2017
DOI: 10.19082/4064
|View full text |Cite
|
Sign up to set email alerts
|

Impact of garlic tablets on nosocomial infections in hospitalized patients in intensive care units

Abstract: BackgroundNosocomial infections are one of the main causes of mortality and morbidity in hospitals, especially in intensive care units (ICUs).ObjectiveThe aim of this study was to examine the impact of garlic tablets on nosocomial infections in hospitalized patients in intensive care units.MethodsThis clinical trial was carried out on 94 patients, admitted to the intensive care units in Kashani and Al-Zahra hospitals from January 21, 2014 to December 20, 2014. Firstly, the patients were randomly selected by si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Garlic tablets at dose 400 mg daily are also a promising candidate for nosocomial infections in hospitalized patients in intensive care units and might be used for the prevention of septicemia and urinary tract infections after six days of treatment [ 137 ]. Furthermore, laboratory studies and clinical trials demonstrated that GE contains organosulfur compounds that exhibit antileishmanial and immunomodulatory activity [ 138 ].…”
Section: Clinical Trials On Garlicmentioning
confidence: 99%
“…Garlic tablets at dose 400 mg daily are also a promising candidate for nosocomial infections in hospitalized patients in intensive care units and might be used for the prevention of septicemia and urinary tract infections after six days of treatment [ 137 ]. Furthermore, laboratory studies and clinical trials demonstrated that GE contains organosulfur compounds that exhibit antileishmanial and immunomodulatory activity [ 138 ].…”
Section: Clinical Trials On Garlicmentioning
confidence: 99%
“…On another note, acupuncture improved the blood pressure of one case study patient (Kreindler et al, 2014). In a sample of 94 patients, garlic tablets successfully treated urinary tract infections in all 47 in the case group (Madineh et al, 2017) and multidrug-resistant…”
Section: Discussionmentioning
confidence: 96%
“…These positive outcomes support the formal inclusion of integrative therapies in ICUs, especially those that improve patient outcomes. Therapies such as garlic tablets may be used to treat bacterial infections in ICUs since garlic is effective against both gram-negative and gram-positive bacteria and acid-fast bacteria such as Salmonella and Helicobacter (Madineh et al, 2017). Garlic tablets are currently classified under herbal medicines which are a form of integrative therapies (Chan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation